2021
DOI: 10.1016/j.psj.2020.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing system and narasin on growth performance, gastrointestinal development, and gut microbiota of broilers

Abstract: This study was conducted to evaluate the effects of 3 rearing systems ( FL : flooring litter rearing, MC : multilayer cage rearing, PN : plastic net rearing) with or without supplemental narasin on growth performance, gastrointestine development and health of broilers. A total of 2,400 one-day-old Ross 308 mixed-sex broilers (1:1 ratio of males and females) were used in a completely randomized design utilizing a 3 × 2 factorial arrangement of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…1). These results agreed with (Yan et al, 2020) who said that that floor rearing usually leads to a richer gut microbiota than other systems. The environmental conditions could alter the gut microbiota, as the FS usually leads to a richer, and more diverse gut microbiota than other systems (Cui et al, 2017).While our results disagreed with (Li et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…1). These results agreed with (Yan et al, 2020) who said that that floor rearing usually leads to a richer gut microbiota than other systems. The environmental conditions could alter the gut microbiota, as the FS usually leads to a richer, and more diverse gut microbiota than other systems (Cui et al, 2017).While our results disagreed with (Li et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The differences may be caused by the change in feed intake of geese. Some studies have found that the changes in the rearing systems will affect the feed intake of poultry ( Starčević et al, 2021 ; Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the majority of colonization of the chick gut with bacteria begins right after hatching via contact with environmental sources at the hatchery, mainly people handling the eggs, transportation boxes, and any feed and water or bedding material available ( Kizerwetter-Świda and Binek, 2008 ; Stanley et al, 2014 ). Young chickens at 1 and 2 d of age are delivered to commercial farms where they are usually placed in bedding material, although rearing of chicks in plastic nets is also practiced in some countries such as China ( Chen et al, 2020 ; Yan et al, 2021 ). Several microbiota taxa from new or reused bedding material and other environmental sources such as feed continue the initial colonization of the gut ( Wang et al, 2016 ).…”
Section: The Microbiota Of the Chicken Intestinal Tractmentioning
confidence: 99%